Respostas
respondido por:
1
Olá Gfz
A = (x + 1/x)² = x² + 2 + 1/x²
B = (x - 1/x)² = x² - 2 + 1/x²
A - B = 4
A + B = A + A - 4 = 2A - 4
(A + B)² = (2A - 4)² = 4A² - 16A + 16
solução inteira
A = 4
B = 0
x = ±1
(A + B)² = 4² = 16
A = (x + 1/x)² = x² + 2 + 1/x²
B = (x - 1/x)² = x² - 2 + 1/x²
A - B = 4
A + B = A + A - 4 = 2A - 4
(A + B)² = (2A - 4)² = 4A² - 16A + 16
solução inteira
A = 4
B = 0
x = ±1
(A + B)² = 4² = 16
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás